Seasonal Survival and Cause-Specific Mortality of Northern Bobwhites in Mississippi - Jimmy D. Taylor II; Loren W. Burger Jr.; Scott W. Manley; Leonard A. Brennan (National Quail Symposium Proceedings, 2017)
Knowledge of northern bobwhite (Colinus virginianus) survival and rates at which specific mortality agents remove individuals from the population is important for implementation of science-based harvest and habitat management regimes. To better understand population response to habitat management, we monitored 194 radio-marked northern bobwhites in managed old-field habitats in eastcentral Mississippi, 1993 to 1996. Bobwhite populations increased during the first 3 years following initiation of disking and burning practices. During the 2nd year of bobwhite habitat management breeding season survival (0.509) was high relative to other southeastern populations. However, breeding season survival declined from the 2nd through the 5th year of management (1993, 0.509; 1994, 0.362; 1995, 0.338; 1996, 0.167; P < 0.001). Declining seasonal survival was attributable to increasing mammalian mortality from 1993 to 1996 (P < 0.01). Avian mortality rates were stochastic and differed among years (P = 0.04), while unknown mortality rates were similar (P = 0.13). Avian mortality evidently operated in a density-dependent fashion, whereas mammalian mortality continued to increase despite declining bobwhite population. Northern bobwhite cause-specific mortality rates among years differed by sex (P < 0.01) and age (P < 0.01). Indices of breeding season relative abundance declined with declining survival. We hypothesize that manipulations (bum, disk, bum/disk) which created habitat that met the seasonal requirements of breeding bobwhites and other early successional prey species, may have resulted in a functional and numerical response of mammalian predators.